2016
DOI: 10.1038/srep34356
|View full text |Cite
|
Sign up to set email alerts
|

Interferon alpha inhibits spinal cord synaptic and nociceptive transmission via neuronal-glial interactions

Abstract: It is well known that interferons (IFNs), such as type-I IFN (IFN-α) and type-II IFN (IFN-γ) are produced by immune cells to elicit antiviral effects. IFNs are also produced by glial cells in the CNS to regulate brain functions. As a proinflammatory cytokine, IFN-γ drives neuropathic pain by inducing microglial activation in the spinal cord. However, little is known about the role of IFN-α in regulating pain sensitivity and synaptic transmission. Strikingly, we found that IFN-α/β receptor (type-I IFN receptor)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 58 publications
0
59
1
2
Order By: Relevance
“…Our findings clearly demonstrate, however, that one of the earliest responses to viral infection, production of type 1 IFN, causes robust and rapid sensitization of nociceptors via a specific translation regulation signaling cascade. Our findings regarding the action of type I IFNs on nociceptors are opposed to the recent work of Liu et al, (Liu et al, 2016) who found that IFNα causes inhibition of pain signaling at the level of the dorsal horn. These authors proposed that type I IFNs from astrocytes cause presynaptic inhibition of neurotransmitter release from nociceptors therefore reducing pain signaling.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings clearly demonstrate, however, that one of the earliest responses to viral infection, production of type 1 IFN, causes robust and rapid sensitization of nociceptors via a specific translation regulation signaling cascade. Our findings regarding the action of type I IFNs on nociceptors are opposed to the recent work of Liu et al, (Liu et al, 2016) who found that IFNα causes inhibition of pain signaling at the level of the dorsal horn. These authors proposed that type I IFNs from astrocytes cause presynaptic inhibition of neurotransmitter release from nociceptors therefore reducing pain signaling.…”
Section: Discussioncontrasting
confidence: 99%
“…These excitatory interneurons express somatostatin (SOM) [40] . We also recorded CCL2 responses in SOM + neurons in lamina IIo of spinal cord slices from transgenic mice showing SOM expression with tdTomato [25] . These neurons were easily identified by bright fluorescence (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also used transgenic C57BL/6 mice (5 weeks) for some electrophysiological experiment. These transgenic mice, obtained from Jackson Laboratory, express tdTomato fluorescence in somatostatin (SOM + ) neurons, after Som -Cre mice were crossed with tdTomato Cre-reporter mice (Rosa26-floxed stop tdTomato mice, Jackson Laboratory), to generate conditional transgenic mice that express tdTomato in SOM + neurons [25] . Adult CD1 mice (male, 8–10 weeks) were used for behavioral and pharmacological studies.…”
Section: Methodsmentioning
confidence: 99%
“…Generated read counts were analyzed in R version 3.4.4 (R Core Team 2018) via Seurat 2.2.1 35 following its standard pre-processing and clustering workflow (https://satijalab.org/seurat/pbmc3k_tutorial.html). Briefly, from the distribution of reads, the data was filtered to a minimum of 300 cells per gene and 30 genes per cell.…”
Section: Clustering Analysis Of Scrna-seq Datamentioning
confidence: 99%